Using Video Recipe to Improve the Junior High School Students’ Ability in Writing Procedure Text - Jupri Jupri (Journal of Languages and Language Teaching, 2019)
Based on the results of a preliminary study, it was found out that the students of SMPN1 Batu have problem in writing procedure texts. The students cannot optimize themselves in written communication in English. To cope with the problem, the researcher conducted an action research Using Video Recipe to Improve the Junior School Students’ Ability in Writing Procedure Text. This action research was done in grade seven of SMPN1 Batu which involved 26 students and has been conducted in one cycle which covered: planning, implementing, observing, and reflecting. The data was obtained through the result of the test, observation checklists, and interview. The study was implemented through four steps: (1) the teacher planned the action based on the result of preliminarystudy, (2) the teacher implemented the action by presenting recipe videos as the model to guide the students in writing procedure text, (3) the observer observed and recorded the action, and (4) the teacher analyzed the data which finally became the reflection of the cycle. The results of the study reveal that the utilization of video recipe can improve the junior high school students’ ability in writing procedure text. Future research in this area should be expanded to examine the nuanced differences in revision based upon different purpose of writing.